The Concept of the DVO Fracture Risk Calculator - Glueer, Claus-C.; Engelke, Klaus; Thomasius, Friederike (Osteologie, 2023)
The estimation of fracture risk is a core task in the care of patients at risk of osteoporosis. Various risk calculators have been developed for this purpose. Despite this, there is a considerable treatment gap of osteoporosis patients, which is also due to insufficient identification of those affected. The DVO Fracture Risk Calculator was developed to improve this situation. In this contribution, the shortcomings of previous risk calculators are listed in order to derive the concept of the DVO Fracture Risk Calculator. Core aspects comprise i) a broad Casefinding strategy via 33 evidence based validated fracture risk factors, ii) the focus on hip and vertebral fracture risk, iii) a calculation of the 3-year fracture risk, optionally with 1-year data in case of high imminent fracture risk, along with iv) bone densitometry at lumbar spine and proximal femur. The risk assessment is based on German reference data. The fracture risk is based on the risk of individuals who do not have any of the clinical risk factors assessed and it is calculated via a sex-specific multiplicative model that takes into account age, the relative risks of the two strongest clinical risk factors and bone densitometry results. The goal is to implement this as an app that will be made available free of charge to DVO osteologists. Until this app is certified, a simplified model in tabular form will be offered for a transitional period. Risk calculators can only support medical expertise of physicians, not replace it, but the DVO Fracture Risk Calculator will hopefully help to reduce the diagnostic gap of osteoporosis patients by helping to identify at-risk patients in an effective way.
CRIS-Team WoS Importer:2023-05-26